2020
DOI: 10.1038/s41388-020-01497-4
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 blockade overcomes acquired resistance to EGFR-TKIs in non-small cell lung cancer

Abstract: The development of resistance to EGFR Tyrosine kinase inhibitors (TKIs) in NSCLC with activating EGFR mutations is a critical limitation of this therapy. In addition to genetic alterations such as EGFR secondary mutation causing EGFR-TKI resistance, compensatory activation of signaling pathways without interruption of genome integrity remains to be defined. In this study, we identified S6K1/MDM2 signaling axis as a novel bypass mechanism for the development of EGFR-TKI resistance. The observation of S6K1 as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…About 5× 10 6 cells were injected subcutaneously into the axilla of the female athymic BALB/C nude mice (4 week-old, 18-20 g). When the average tumor size reached approximately 100mm 3 (after 1 week), mice were then randomized into two groups and treated with cisplatin (5 mg/kg) or normal saline (NS) weekly. Tumor width (W) and length (L) was measured every week, and the volume (V) of the tumor was calculated as the formula V = (W 2 × L)/2.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…About 5× 10 6 cells were injected subcutaneously into the axilla of the female athymic BALB/C nude mice (4 week-old, 18-20 g). When the average tumor size reached approximately 100mm 3 (after 1 week), mice were then randomized into two groups and treated with cisplatin (5 mg/kg) or normal saline (NS) weekly. Tumor width (W) and length (L) was measured every week, and the volume (V) of the tumor was calculated as the formula V = (W 2 × L)/2.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Several mechanisms, including activation of oncogenes, mutation of antioncogene, and dysregulation of cancer-associated signaling pathway, are involved in chemoresistance [3][4][5]. N6-methyladenosine (m6A) modification is one of the most prevalent mRNA modification and influences mRNA transcription, stabilization, and translation [6].…”
Section: Introductionmentioning
confidence: 99%
“…4F). Indeed, this bioinformatic result is supported by the observation that MDM2 mediates resistance to EGFR inhibitors in mouse models of NSCLC (Shen et al ., 2020). Furthermore, our analysis of BRAF inhibitor sensitivity suggested that tumors sensitive to BRAF inhibitors would also be sensitive to MEK inhibitors (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have reported that the gain of function is the central role of RPS6KB1 in resistance to tyrosine kinase (TKI) in lung cancer, and its specific inhibitor PF-4708671 shows synergistic effect to enhance TKIs efficacy to suppress tumor growth in vivo [ 33 ]. Several studies have shown that single reagent treatment often fails in clinical practice, additional studies are necessary to optimize combination therapies that include RPS6KB1 inhibitor to treat EC.…”
Section: Discussionmentioning
confidence: 99%